Cognitive Function and Functional Ability of Older People, Elderly School, Faculty of Nursing, Ubon Ratchathani University - สิงหาด สาวิตรี; กิตติวรเวช สุฬดี; มีนาเขตร ภูษณิศา; สุริยา อธิพงศ์ (Journal of Health Science of Thailand, 2021)
The purpose of the study was to investigate cognitive function and functional ability of older people in the Elderly School, Faculty of Nursing, Ubon Ratchathani University. Samples of 90 older people were selected through purposive sampling. The instruments used for the collected data included general information form, mini-mental state examination tool (Thai version 2002), and functional ability assessment form. Data were analyzed by using descriptive statistics. percentage, mean, standard deviation. The results showed that 84.4% of the older people had normal cognitive function; and 15.6% had a risk for dementia (Mean=20.42, SD=1.36). Assessment of functional ability of the elderly revealed that the sample could help themselves in the daily living activities (Mean=18.25, SD=0.68); and could help themselves in the instrumental activity of daily index (Mean=7.75, SD=0.56). The results of this study could be used as a basis for developing projects and activities to reduce degeneration, maintain physical function, and prevent dementia among the elderly; and to promote their health for a better quality of life